2016
DOI: 10.1007/s00726-016-2278-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycine inhibits angiogenesis in colorectal cancer: role of endothelial cells

Abstract: Neo-angiogenesis is important for tumor growth. Glycine is a non-toxic amino acid with suspected anti-angiogenic effects. This study was designed to evaluate anti-angiogenic effects of glycine in colorectal cancer. Glycine was added to cultures of human and rat colorectal cancer cells (CRC), and endothelial cells (HUVEC). Glycine's direct impact was monitored using MTT assays. Angiogenesis in HUVEC was monitored using 3D sprouting and migration assays. VEGF and CRC-conditioned media were used to stimulate angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
3
26
0
2
Order By: Relevance
“…Herein, we have observed anticancer effects of high concentrations of glycine and D‐serine (from 2 mM up to 532 mM) toward osteosarcoma 143B cells. Indeed, in correlation with our studies, glycine was shown to possess antiangiogenic effect on wound healing, induced liver tumors, melanoma, and mammary cancer in vivo (Bruns et al, , ). Moreover, in vivo experiments demonstrated reduction of growth rate and final volume of colorectal tumors after treatment with 1 mM glycine (Bruns et al, , ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Herein, we have observed anticancer effects of high concentrations of glycine and D‐serine (from 2 mM up to 532 mM) toward osteosarcoma 143B cells. Indeed, in correlation with our studies, glycine was shown to possess antiangiogenic effect on wound healing, induced liver tumors, melanoma, and mammary cancer in vivo (Bruns et al, , ). Moreover, in vivo experiments demonstrated reduction of growth rate and final volume of colorectal tumors after treatment with 1 mM glycine (Bruns et al, , ).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, in correlation with our studies, glycine was shown to possess antiangiogenic effect on wound healing, induced liver tumors, melanoma, and mammary cancer in vivo (Bruns et al, , ). Moreover, in vivo experiments demonstrated reduction of growth rate and final volume of colorectal tumors after treatment with 1 mM glycine (Bruns et al, , ). These observations provide further support that glycine might be a useful antiangiogenic and antitumor agent (Bruns et al, , ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In recently published studies, glycine has been shown to prevent KC-dependent liver injury in chemotherapy models and inhibit angiogenesis in hepatocellular carcinoma and colorectal cancer [16][17][18]. Thus, we hypothesized that preconditioning with glycine before pneumoperitoneum prevents the activation of KCs and related phenomena, like disturbances in the hepatic microcirculation after pneumoperitoneum.…”
Section: Introductionmentioning
confidence: 99%